The influence of e-commerce and public relations on sales at PT. Indonesian Property Map - Elbert, Elbert; Irwansyah Djali (Paspama Institute, 2024)
PT Peta Property Indonesia is located on Jl. Sutrisno no. 54, Kotamatsum III, District. Medan City, Medan City, North Sumatra 20211, Indonesia. PT Peta Property Indonesia operates as a distributor selling housing. The company was unable to achieve its housing sales target and sales tended to decline in September and October 2022. Employees also interacted less with consumers via telephone. During this pandemic, consumers reduced demand for housing so that the level of housing sales was low. The purpose of this study was to test and analyze e-commerce and public relations on sales at PT. Indonesian Property Map. The type of data used by researchers in this study are: quantitative data originating from the results of respondents' answers to the questionnaire. The population is 242 customers of PT. Indonesian property map. The sample is 71 customers of PT. Indonesian property map. Multiple linear regression is a linear relationship between two or more independent variables (X) and the dependent variable (Y). The result of this research is that E-commerce has an effect on sales at PT. Indonesian Property Map. Public relations have an effect on sales at PT. Indonesian Property Map. E-commerce and public relations have an effect on sales at PT. Indonesian Property Map.